Welfare Chauvinism - Svirbutaitė-Krutkienė, Giedrė; Guogis, Arvydas (Socialinė teorija, empirija, politika ir praktika, 2019)
The authors in the article reveal the positioning of extreme right political parties in the Western world and Central and Eastern Europe by following such ideological basis as nationalism and welfare chauvinism, practically rejecting immigrants and their willingness to use the benefits and services of the mentioned welfare systems in the presented Western as well as Central and Eastern European countries. The authors maintain their position, applying the secondary data from European Social Survey, International Monetary Fund and OECD data as well as interpretations of the authors from different foreign countries. In the end of the article the authors pose the one of the most interesting scientific and practical questions – why the place of the electorate of the „socially excluded“ and having low income voters is moving from the left political parties to the side of the extreme right political parties? The further research is necessary in the following direction. This article is the first article of the theme on social chauvinism in Lithuania.
Keywords: right wing extremist political parties; welfare chauvinism; nationalism; welfare states; social benefits; social services